Responses of phytoplankton communities driven by differences of source water intrusions in the El Niño and La Niña events in the Taiwan Strait during the early spring - Zhong, Yanping; Laws, Edward A.; Zhuang, Jiafu; Wang, Jingxiao; Wang, Peixuan; Zhang, Caiyun; Liu, Xin; Huang, Bangqin (Frontiers in Marine Science, 2022)
The El Niño Southern Oscillation (ENSO) is one of the most important drivers of interannual variations of marine ecosystems, especially monsoonal ecosystems. The channel effect in a strait amplifies the impact of monsoons and may be an ideal area to study ecosystem responses to ENSO events. Previous studies have shown that physical processes in the Taiwan Strait (TWS) vary during the different ENSO phases, but the biological responses are still unclear. In this study, we found clear differences in the physical, chemical, and biological characteristics of the TWS between different ENSO phases based on data from satellites and field cruises during the 2015–2016 El Niño and 2017–2018 La Niña events. Although the monsoonal patterns were similar during early spring cruises during two ENSO events, the influence of the China Coastal Current (CCC), which is characterized by low sea surface temperature, low salinity, and high nutrient concentrations, was 1.5 times greater during the 2015–2016 El Niño than the 2017–2018 La Niña. The average chlorophyll a concentration was therefore higher in 2016 than that in 2018. The phytoplankton consisted mainly of diatoms, dinoflagellates, and cryptophytes during the 2015–2016 El Niño, but concentrations of those phytoplankton groups decreased during the 2017–2018 La Niña, and concentrations of prasinophytes, Synechococcus, and Prochlorococcus increased. Their influence of the CCC and warm currents were associated with the variations in phytoplankton community structure in the TWS. The results of this study enhance understanding of the responses of marine ecosystems to climate variabilities, and of the changes that climate change may bring to strait ecosystems.